The transformation of agriculture in China: Looking back and looking forward - Xiao-qiang JIAO; Nyamdavaa Mongol; Fu-suo ZHANG (Journal of Integrative Agriculture)
China's grain yield increased from 1 t ha−1 in 1961 to 6 t ha−1 in 2015, while successfully feeding not only its large population but also supplying agricultural products all over the world. These achievements were greatly supported by modern technology and distinct governmental policy. However, China's grain production has been causing a number of problems mainly related to declining natural resources and a lack of environmental protection. Due to the growing population and changing dietary requirements, increasing food production must be achieved by increasing resource use efficiency while minimizing environmental costs. We propose two novel development pathways that can potentially sustain agricultural crop production in the next few decades: (i) enhancing nutrient use efficiency with zero increase in chemical fertilizer input until 2020 and (ii) concurrently increasing grain yield and nutrient use efficiency for sustainable intensification with integrated nutrient management after 2020. This paper provides a perspective on further agricultural developments and challenges, and useful knowledge of our valuable experiences for other developing countries.